The Effectiveness of Azadirachta indica A. Juss. and Barringtonia Asiatica L. Kurz. Seed Extract to Controlling Macrosiphoniella sanborni (Hemiptera : aphididae) on Chrysanthemum Morifolium Var. Jayanti - Masturina, Safirah Amalia; Sudarjat, Sudarjat; Nasahi, Ceppy (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
Macrosiphoniella sanborni is a main concern in the production of ornamental chrysanthemum plants. Farmers commonly use chemical treatment to control aphids, but this can harmful the environment and humans. Therefore, alternative environmentally control is needed, one of which is by using botanical pesticides such as Azadirachta indica and Barringtonia asiatica. This research aimed to test the effectiveness of the neem and bitung seed extract against M. sanborni pests on chrysanthemum plants. This research was conducted at the Chrysanthemum cultivation Mr. Syarif’s screen house in Karyawangi village, Parongpong district, West Java, which began in January 2021 to May 2021. This research used an experimental method using a Randomized Complete Block Design (RCBD) which each experiment consisted of 10 treatments and each treatment was repeated 3 times. The tested treatments are neem and bitung seed extract in different concentration, and controls. The results of this study revealed that the effective treatment of M. sanborni on chrysanthemum is the extract of bitung seed at the concentration of 2%. Bitung seed extract pesticides can be used as an alternative synthetic pesticide to control population of M. sanborni.